Công văn của Bộ Nội vụ về việc trả lời chất vấn của Đại biểu Quốc hội tại Kỳ họp thứ 2 Quốc hội khóa XIV (Số: 5964/BNV-TCBC) - Bộ Nội vụ (2016)
Công văn của Bộ Nội vụ về việc trả lời chất vấn của Đại biểu Quốc hội tại Kỳ họp thứ 2 Quốc hội khóa XIV (Số: 5964/BNV-TCBC) ngày 15/12/2016